2023
DOI: 10.3390/plants12213679
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Biofilm Activity of Carnosic Acid from Salvia rosmarinus against Methicillin-Resistant Staphylococcus aureus

Valeria Iobbi,
Valentina Parisi,
Giulia Bernabè
et al.

Abstract: The Salvia rosmarinus “Eretto Liguria” ecotype was studied as a source of valuable bioactive compounds. LC-MS analysis of the methanolic extract underlined the presence of diterpenoids, triterpenoids, polyphenolic acids, and flavonoids. The anti-virulence activity of carnosic acid along with the other most abundant compounds against methicillin-resistant Staphylococcus aureus (MRSA) was evaluated. Only carnosic acid induced a significant reduction in the expression of agrA and rnaIII genes, which encode the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Later on, these diterpenoids from the leaves of S. officinalis were found to have antioxidant and antibacterial activities [108]. Recently, carnosic acid was shown to suppress the development of oral squamous cell carcinoma via the mitochondrial apoptotic pathway [120] and to prevent the biofilm formation of methicillin-resistant Staphylococcus aureus (MRSA) [121]. Recent studies have demonstrated its potential as a preventive agent against soft rot caused by Pectobacterium carotovorum subsp.…”
Section: Abietane Diterpenoids: Carnosic Acid and Carnosolmentioning
confidence: 99%
“…Later on, these diterpenoids from the leaves of S. officinalis were found to have antioxidant and antibacterial activities [108]. Recently, carnosic acid was shown to suppress the development of oral squamous cell carcinoma via the mitochondrial apoptotic pathway [120] and to prevent the biofilm formation of methicillin-resistant Staphylococcus aureus (MRSA) [121]. Recent studies have demonstrated its potential as a preventive agent against soft rot caused by Pectobacterium carotovorum subsp.…”
Section: Abietane Diterpenoids: Carnosic Acid and Carnosolmentioning
confidence: 99%